Application of PCR-based serogrouping of selected Salmonella serotypes in Malaysia - Lim, B.K.; Thong, Kwai Lin (2009)
Based on this study, PCR serogrouping proved to be a rapid, alternative method for further differentiation of Salmonella enterica.